2015
DOI: 10.1007/s40261-015-0333-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Transcatheter Arterial Chemoembolization Followed by Sorafenib for Intermediate/Advanced Hepatocellular Carcinoma in Patients in Japan: A Retrospective Analysis

Abstract: BackgroundSorafenib might prevent hepatocellular carcinoma (HCC) recurrence caused by the promotion of neoangiogenesis after transarterial chemoembolization (TACE).ObjectivesTo evaluate the efficacy and safety of TACE followed by sorafenib for treating advanced HCC.Patients and MethodsWe retrospectively analyzed 95 advanced HCC patients treated with TACE between July 2008 and December 2012 at our institution. Twenty-four patients received TACE followed by sorafenib within 14 days (S-TACE) and 71 received TACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Many clinical trials also have shown that combination therapy can prolong OS [4, 6, 1113]. The heterogeneity of patients’ physical conditions may be the primary factor affecting OS, as candidate selection may make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials also have shown that combination therapy can prolong OS [4, 6, 1113]. The heterogeneity of patients’ physical conditions may be the primary factor affecting OS, as candidate selection may make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were further supported by two meta-analyses of randomized controlled trials, published by Zhang et al21 and Fu et al9 Moreover, SOR also showed significantly improved OS and TTP in patients with intermediate or advanced HCC that is refractory to TACE 10,22,23…”
Section: Introductionmentioning
confidence: 60%
“…A previously published case series reported the beneficial effects of SOR for the treatment of TACE-refractory HCC 10. In addition, a retrospective study showed that the DCR for SOR was 60.4%, the median TTP was 3.9 months, and the median OS was 16.4 months in patients who were refractory to TACE 22.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies compared sorafenib plus TACE to sorafenib or TACE [72][73][74][75][76][77][78] [Supplementary Table 4]. A meta-analysis of sorafenib in combination with TACE that included data of 1,254 patients found that the combination improved OS and TTP in advanced HCC, but not PFS, with higher rate of severe adverse reaction in the combination group.…”
Section: Combination Of Targeted Therapy With Locoregional Therapymentioning
confidence: 99%